2023
DOI: 10.31083/j.rcm2406177
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Takotsubo Syndrome in Acute Aneurysmal Subarachnoid Hemorrhage: A Comprehensive Review

Abstract: Takotsubo syndrome (TS) is a frequent complication of subarachnoid hemorrhage (SAH), especially in massive SAH with severe neurological damage. The initial presentation of TS is similar to acute coronary syndrome, causing differential diagnostic issues. Unnecessary diagnostic steps and uncertainty in therapy may delay the definitive treatment of the aneurysm, therefore increasing the risk of rebleeding. The purpose of this review is to summarize the latest knowledge on the diagnosis and therapy of TS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…The predefined threshold of 40% ejection fraction (EF) was based on previous reports indicating that the critical value of EF that determines cardiovascular complications lies between 40 and 45%. Catecholamine release triggered by the ictus plays a central role in the pathophysiology of TTC [14]. Catecholamines also trigger peripheral immune cell recruitment; thus, higher immune cell peaks may reflect a more intense catecholamine surge and may draw attention to the higher risk of TTC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predefined threshold of 40% ejection fraction (EF) was based on previous reports indicating that the critical value of EF that determines cardiovascular complications lies between 40 and 45%. Catecholamine release triggered by the ictus plays a central role in the pathophysiology of TTC [14]. Catecholamines also trigger peripheral immune cell recruitment; thus, higher immune cell peaks may reflect a more intense catecholamine surge and may draw attention to the higher risk of TTC.…”
Section: Discussionmentioning
confidence: 99%
“…The pathomechanism of TTC is not completely understood, but catecholamine-induced myocardium stunning seems to have a prominent role. There is also growing evidence for the pathogenetic role of inflammatory mechanisms, reflected by generally elevated C-reactive protein in TTC [13,14]. Recent studies revealed that systemic inflammation might have important pathogenic and prognostic implications in the general TTC patient population [15]; however, data on SAH-associated TTC are lacking.…”
Section: Introductionmentioning
confidence: 99%